Economic Dimensions of Agrarian Contracting - BACHEV, Hrabrin (Theoretical and Practical Research in Economic Fields, 2024)
The achievements of the interdisciplinary New Institutional Economics are adapted and a holistic approach to the definition, classification, evaluation, and improvement of contracts and contractual relations is justified. A critical analysis of the contemporary development of Contractual Economics is made and the specificity of the economic study of agrarian contracts is summarized. A ‘new’ Agents-Means-Process-Order (AMPO) approach for economic analysis, evaluation and improvement of agrarian contracts is presented, including: (1) economic definition of agrarian contracts and characterization of their place in the system of agrarian governance as bilateral or multilateral agreements related to agricultural production and services; (2) economic characteristics of the agents participating in the contractual relations (interests, awareness, risk-taking, capability, tendency to opportunism, etc.); (3) economic characteristics of different types of agrarian contracts (for purchase and sale, hire of labor and resources, services, loan, insurance, marketing, coalition, etc.); (4) economic characterization of the agrarian contracting process (technological, transactional, institutional, etc. factors for managerial choice); (5) economic characterization of the outcome of the contractual process and the dominant governance order in the agrarian sphere (rule of law, rule of force, contractual structure, etc.); (6) characterization of the stages for the improvement of agrarian contracts and governance (identification of problems and failures of the market, private contracting, and public modes; needs and forms of new public intervention, etc.); (7) identification of needs and sources of new information for analysis and evaluation of agrarian contracts.